Anthropology and Mass Communication - Mark Allen Peterson (Berghahn Books, 2003)
I have dabbled in media at least since junior high school, when my father bought me a used 8mm movie camera. My productions were fundamentally intertextual, pastiches and parodies of the television and films I enjoyed viewing. They were also fundamentally social activities, ways for a loud, socially inept adolescent to bring together a group of male and female comrades, some of whom might not otherwise have wanted anything to do with me. I went to Mayo High School in Rochester, Minnesota, one of the first secondary schools in America to have a fully fledged television production studio, and at sixteen I was producing (with a crew of six) a daily, two-minute humorous segment for the schoolâ€™s daily ten-to-fifteen minute broadcast, The Spartan Scene. While an undergraduate majoring in the study of religion at UCLA, I freelanced for magazines and newspapers, and discovered a lucrative niche producing institutional newsletters. I was hired to write a screenplay treatment for a movie about King David, which was never made (the funding collapsed when Variety announced Dino DeLaurentis was planning a movie on the same subject starring Richard Gere). Accompanying my wife to the east coast to pursue her M.Ed., I learned computer typesetting as a text editor for law books at the Michie Company in Virginia. When my wife found a job in Washington, DC, I began taking classes in anthropology at the Catholic University of America, and I became assistant editor of Anthropological Quarterly. Needing a job, I lucked into an assistant editorial position at the National Tribune Co., where for three years I learned the mysteries of the Washington Press Corps. The â€œTrib,â€ as we affectionately called it, published watchdog publications on the U.S. Department of Veterans Affairs (and its predecessors), several congressional committees and some departments of the Pentagon. It was a great place to work. Hours were flexible, pay was low, and turnover high; an assistant editor might find himself off to cover a congressional hearing or interviewing a senator because no reporters were available.